High-spectral-resolution Observations of the Optical Filamentary Nebula Surrounding NGC 1275 - Benjamin Vigneron; Julie Hlavacek-Larrondo; Carter Lee Rhea; Marie-Lou Gendron-Marsolais; Jeremy Lim; Jake Reinheimer; Yuan Li; Laurent Drissen; Greg L. Bryan; Megan Donahue; Alastair Edge; Andrew Fabian; et al. (The Astrophysical Journal, 2024)
We present new high-spectral-resolution observations ( R = λ /Δ λ = 7000) of the filamentary nebula surrounding NGC 1275, the central galaxy of the Perseus cluster. These observations have been obtained with SITELLE, an imaging Fourier transform spectrometer installed on the Canada–France–Hawai Telescope with a field of view of $11^{′} × 11^{′} $ , encapsulating the entire filamentary structure of ionized gas despite its large size of 80 kpc × 50 kpc. Here, we present renewed fluxes, velocities, and velocity dispersion maps that show in great detail the kinematics of the optical nebula at [S ii ] λ 6716, [S ii ] λ 6731, [N ii ] λ 6584, H α (6563 Å), and [N ii ] λ 6548. These maps reveal the existence of a bright flattened disk-shaped structure in the core extending to r ∼10 kpc and dominated by a chaotic velocity field. This structure is located in the wake of X-ray cavities and characterized by a high mean velocity dispersion of 134 km s ^−1 . The disk-shaped structure is surrounded by an extended array of filaments spread out to r ∼ 50 kpc that are 10 times fainter in flux, remarkably quiescent, and have a uniform mean velocity dispersion of 44 km s ^−1 . This stability is puzzling given that the cluster core exhibits several energetic phenomena. Based on these results, we argue that there are two mechanisms that form multiphase gas in clusters of galaxies: a first triggered in the wake of X-ray cavities leading to more turbulent multiphase gas and a second, distinct mechanism, that is gentle and leads to large-scale multiphase gas spreading throughout the core.